Jenis Persalinan dengan Waktu Pengeluaran Kolostrum Pada Ibu Bersalin Kala IV di Kota Yogyakarta - Almas Azifah Dina; Sumarah Sumarah; Ana Kurniati (Jurnal Kesehatan Ibu dan Anak, 2017)
RETRACTED Following rigorous and careful concerns and consideration in the review of the article published in Jurnal Kesehatan Ibu dan Anak entitled “Jenis Persalinan dengan Waktu Pengeluaran Kolostrum Pada Ibu Bersalin Kala IV di Kota Yogyakarta” Vol 11, No 2, November 2017, DOI: https://doi.org/10.29238/kia.v11i2.39 The article has contained redundant material and throughout a careful examination, the editor has found that the paper has also been published in Jurnal Teknologi Kesehatan, Vol. 13, No. 1, Maret 2017 This paper has been found to violate the principles of Jurnal Kesehatan Ibu dan Anak publication and has been retracted.